2014
DOI: 10.3390/e16126415
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Chaos from Agricultural Product Price Time Series

Abstract: Analysis of the characteristics of agricultural product price volatility and trend forecasting are necessary to formulate and implement agricultural price control policies. Taking wholesale cabbage prices as an example, a multiple test methodology has been adopted to identify the nonlinearity, fractality, and chaos of the data. The approaches used include the R/S analysis, the BDS test, the power spectra, the recurrence plot, the largest Lyapunov exponent, the Kolmogorov entropy, and the correlation dimension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…According to Table 4, under the condition that equals one and = 0 and = 0, there are five possible local equilibrium points of the evolutionary game in the plane {( , ) | 0 ≤ , ≤ 1}, including (0, 0), (0, 1), (1, 0), (1,1), and ( * , * ). The point ( * , * ) is the saddle point which is subject to the condition that = = 0.…”
Section: Replicator Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 4, under the condition that equals one and = 0 and = 0, there are five possible local equilibrium points of the evolutionary game in the plane {( , ) | 0 ≤ , ≤ 1}, including (0, 0), (0, 1), (1, 0), (1,1), and ( * , * ). The point ( * , * ) is the saddle point which is subject to the condition that = = 0.…”
Section: Replicator Dynamicsmentioning
confidence: 99%
“…Numerous scholars have discussed effective countermeasures to shield innocent consumers from quality opportunistic behaviors within the conceptual frameworks of institutional economics, customer behaviors, game theory, and so forth. It has been revealed that cooperation between producers and marketers would improve and maintain the agri-food quality, but owing to the market risks coming from information asymmetry and consumers' cognitive limitation, the cooperation for improving and maintaining agri-food quality might be vulnerable [1,2]. The existing researches draw a key question of how to ensure the cooperation between producers and marketers for quality improvement in such uncertain environments.…”
Section: Introductionmentioning
confidence: 99%
“…Fanti et al [7] discussed the dynamics of a nonlinear Cournot duopoly with managerial delegation. Su et al [8] applied a multiple test methodology to identify the nonlinear, fractal, and chaotic characteristics in the agricultural price system. These researches demonstrate that the agricultural product circulation is somehow a complex system, which has the distinct properties such as nonlinearity, emergence, spontaneous order, and adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of game economic equilibrium is derived. Taking the wholesale price of Chinese cabbage as an example, Su et al [2] identified the non-linearity, fractal and chaos of the data by means of multivariate test. It is found that there is some confusion in the wholesale price data of agricultural products in China.…”
Section: Introductionmentioning
confidence: 99%